2014
DOI: 10.1002/elan.201300449
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Polymer Ion‐Selective Membrane Electrode Surfaces

Abstract: Membrane/sample interactions play a crucial role in the biomedical application of ion selective electrodes (ISEs). Modulation of membrane surface properties can be used as a way to enhance biocompatibility and in fabrication of biosensors through biomolecules immobilization. This review discusses advances in methods and materials used for the surface modifications of polymeric ion-selective membranes in view of their applications in clinical diagnostics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 114 publications
(164 reference statements)
0
24
0
Order By: Relevance
“…During the past decades, several strategies have been proposed to improve the biocompatibility of polymeric membrane ISEs in order to make them reliable for continuous blood sample analysis and even the eventual monitoring in vivo. 10 These attempts have made great contributions toward the improvement of the biocompatibility, but the developed sensors are usually involved with complicated synthesis processes or unstable surface modification layers. This poses serious limits to their wide use, especially for long-term in vivo monitoring.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…During the past decades, several strategies have been proposed to improve the biocompatibility of polymeric membrane ISEs in order to make them reliable for continuous blood sample analysis and even the eventual monitoring in vivo. 10 These attempts have made great contributions toward the improvement of the biocompatibility, but the developed sensors are usually involved with complicated synthesis processes or unstable surface modification layers. This poses serious limits to their wide use, especially for long-term in vivo monitoring.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Schaubroeck et al have shown that addition of amine groups to dielectric resins improves the adhesion with electrochemically deposited metals (Figure c) . Treatment of polymer surfaces with strong electron affinity groups, such as fluorine via solution reactions or chemical vapor treatments enhances their electron acceptance . The triboelectric polarities of polymers are enhanced with selective functionalization with positively and negatively charged reactive species which are covalently bonded to the polymer surface (Figure b).…”
Section: Chemical Treatment On Polymersmentioning
confidence: 99%
“…Reports on haemocompatible sensor surfaces still indicate a continued quest for the single 'magic bullet' solution where none may exist. Nevertheless, general rules may be derived from such studies, such as general rules for hydrophobic/hydrophilic balance for lowered fouling and specific surface chemical motifs that link to complement activation [43]. The surface protein profile together with its later remodeled form [44] presents the real final contact layer for all the subsequent cellular processes organised by blood.…”
Section: Protein Surface Interactionsmentioning
confidence: 99%